Faktor-Faktor yang Mempengaruhi Pengetahuan tentang Bantuan Hidup Dasar pada Tim Pemadam Kebakaran dan Penyelamatan Kota Bengkulu - Pawiliyah Pawiliyah; Fernalia Fernalia; Anugerah Aprioni (Jurnal Keperawatan Silampari, 2023)
This study aims to determine the factors that influence knowledge about BLS in the fire and rescue team in Bengkulu City. This research method uses a cross-sectional approach with the type of analytical survey research. The sample in this study amounted to 63 people, and bivariate data analysis using the regression coefficient test. The results showed that the value of the t statistic for the length of work variable was 3,330 with a p-value = 0.001 (Î± < 0.05), and the t statistic for the education level variable was 4,149 with a p-value = 0.000. In conclusion, research proves that length of work and level of education influence knowledge about BLS in fire and rescue teams in Bengkulu City. Keywords: BLS, Length of Work, Education, Knowledge